Avaliação objetiva dos defeitos superficiais de pavimentos flexíveis e semi-rígidos: estudo de caso Campus do Guamá da UFPA - AVELAR, Carlos Henrick dos Reis (2025)
The analysis of surface defects in the pavements of the Guamá Campus at UFPA used the Pavement Condition Index (PCI) method based on the SHRP (Strategic Highway Research Program) to evaluate pavement conditions and identify key pathologies affecting quality and safety. The objective was to classify sections as ranging from excellent to poor condition, providing a reliable quantitative basis for guiding maintenance and rehabilitation actions. The study is justified by the importance of efficient public resource management, with planned interventions to extend pavement lifespan and ensure user safety. The method included field surveys of visible defects, detailed mapping, and PCI calculations for each section, following SHRP criteria, which consider defect types and severity. The analysis revealed PCI values ranging from 68.33 to 90.83 across the 14 evaluated sections, with an average of 76.13, indicating the need for preventive and corrective repairs to maintain adequate conditions. Recommended interventions range from crack sealing and minor repairs on sections in good condition to more extensive rehabilitations on significantly deteriorated roads. It is concluded that implementing a Pavement Management System (PMS) is essential for proactive maintenance on the university campus. Suggestions for future studies include applying emerging technologies for continuous and automated monitoring of road conditions, allowing for more precise and sustainable planning for university infrastructure.